2020
DOI: 10.1177/1535370220934039
|View full text |Cite
|
Sign up to set email alerts
|

Label-free characterization of collagen fibers in cancerous esophagus tissues using ratiometric nonlinear optical microscopy

Abstract: A quantitative analytical method to discriminate among the various types of cancerous esophagus tissue is essential for accurate cancer staging. This paper reports on the use of ratiometric nonlinear optical microscopy to reveal the ratio of two-photon excited fluorescence (TPEF) to second harmonic generation (SHG) and forward to backward (F/B) SHG from single collagen fibers only in submucosa of esophageal squamous cell carcinoma. This makes it possible to accurately differentiate among the four stages of eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Furthermore, SHG/CARS microscopy was used to investigate the molecular structure and denaturation degree of collagen between these crosslinked materials. For the prospects of using NLO microscopy, it has the potential as a diagnostic tool for the structural organization of collagen in bone-engineered materials and hence can lead to early diagnosis of collagen-related diseases (Mostaço-Guidolin et al, 2017;Chen et al, 2020). For clinical applications, it can be translated into nonlinear endomicroscopy (Lin et al, 2018;Zhuo et al, 2020) benefited from cheap and high-power femtosecond fiber laser systems to perform real-time and deep-tissue intravital imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SHG/CARS microscopy was used to investigate the molecular structure and denaturation degree of collagen between these crosslinked materials. For the prospects of using NLO microscopy, it has the potential as a diagnostic tool for the structural organization of collagen in bone-engineered materials and hence can lead to early diagnosis of collagen-related diseases (Mostaço-Guidolin et al, 2017;Chen et al, 2020). For clinical applications, it can be translated into nonlinear endomicroscopy (Lin et al, 2018;Zhuo et al, 2020) benefited from cheap and high-power femtosecond fiber laser systems to perform real-time and deep-tissue intravital imaging.…”
Section: Discussionmentioning
confidence: 99%
“…PI-SHG microscopy was also used to image submucosa of esophageal squamous cell carcinoma (ESCC). The ρ values from 4 stages of ESCC showed few differences between one another, and (2) zzz , χ (2) zxx , χ (2) zxz , χ (2) xxx , χ (2) xzz , and χ (2) xxz : NR [ authors concluded that PI-SHG microscopy cannot be used for staging ESCC because the structural changes are likely of macromolecular rather than micromolecular origin [42].…”
Section: Applications Of Shg Microscopy For Determining the Ultrastructure Of Diseased Collagenous Tissues Polarization-in Shg Microscopymentioning
confidence: 99%